Photo‐biocatalytic One‐Pot Cascades for the Enantioselective Synthesis of 1, 3‐Mercaptoalkanol Volatile Sulfur Compounds. Issue 20 (14th April 2018) - Lauder, Kate; Toscani, Anita; Qi, Yuyin; Lim, Jesmine; Charnock, Simon J.; Korah, Krupa; Castagnolo, Daniele
Abstract: The synthesis of enantiomerically pure 1, 3‐mercaptoalkanol volatile sulfur compounds through a one‐pot photo‐biocatalytic cascade reaction is described. Two new KRED biocatalysts with opposite enantioselectivity were discovered and proved to be efficient on a wide range of substrates. The one‐pot cascade reaction combining photocatalytic thio‐Michael addition with biocatalytic ketoreduction in an aqueous medium provides a green and sustainable approach to enantiomerically pure 1, 3‐mercaptoalkanols in high yields with excellent enantioselectivity. Abstract : A dependable route to volatile products : A one‐pot cascade reaction combining photocatalytic thio‐Michael addition with biocatalytic ketoreduction in an aqueous medium was developed for the synthesis of enantiomerically pure 1, 3‐mercaptoalkanols (see scheme). Two new ketoreductase (KRED) biocatalysts with opposite enantioselectivity were discovered and found to reduce a wide range of substrates efficiently.